Peran Progam Wali Asuh dalam Membentuk Kedisiplinan Santri Pondok Pesantren Al Mahrusiyah Putra Lirboyo - Iqbal Karim; Ahmad Masrukin (Indonesian Journal of Humanities and Social Sciences, 2020)
This study used a qualitative approach with field research conducted at Pondok Pesantren Al Mahrusiyah Putra Lirboyo, Kediri City. This study aims to examine the impact of the foster care program in shaping the discipline of students at the Al-Mahrusiyah Islamic Boarding School. This study departs from two research questions, namely how the program carried out by foster caregivers in shaping the discipline of students and how is the impact of the program of foster care in shaping the discipline of students. By using the method of observation, interviews, and documentation the researcher can conclude from the results of the study that the role of foster care is very important to help the success of the boarding school program, especially in terms of forming student discipline. As in the program he established, among others: rote deposits, congregations praying dhuha, pickets of cleanliness. The program that has been compiled by foster caregivers to form student discipline can be said to have been in accordance with the factors that affect a person's discipline, which in contact with these factors will affect the discipline of the students.